FINANCIAL FEASIBILITY STUDY FOR “SPASI” CONCESSION PROJECT AT PT. WIJAYA KARYA BANGUNAN GEDUNG TBK (The Indonesian Journal of Business Administration, 2021)
To develop the capabilities of Engineering, Procurement and Construction (EPC) to undergo the opportunity to work on projects from Government, Private, and International. In order to support the running process of state infrastructure, PT. Wijaya Karya Gedung Gedung Tbk. in collaboration with PT. Bank Mandiri to establish an agreement to create a pop-up mall “SPASI” to support the surrounding economy through infrastructure. However, due to the Covid-19 Pandemic, the mall industry experienced a decrease in occupancy rate to 82.9% which caused the SPASI project needed to be reviewed. Keywords: PT. Wijaya Karya Bangunan Gedung Tbk., Capital Structure, SPASI, Debt Ratio, Construction Project Scheduling